2019
DOI: 10.31661/jbpe.v0i0.700
|View full text |Cite
|
Sign up to set email alerts
|

An Android Application for Estimating Muscle Onset Latency using Surface EMG Signal

Abstract: Background: Electromyography (EMG) signal processing and Muscle Onset Latency (MOL) are widely used in rehabilitation sciences and nerve conduction studies. The majority of existing software packages provided for estimating MOL via analyzing EMG signal are computerized, desktop based and not portable; therefore, experiments and signal analyzes using them should be completed locally. Moreover, a desktop or laptop is required to complete experiments using these packages, which costs.Objective: Develop a non-expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Therefore, regardless of sex, it is striking that most of the muscle activation outcomes analyzed in the studies included in this review demonstrated no significant changes. It is possible that certain limitations related to assessment techniques (e.g., sensitivity of the equipment used to measure sEMG, use of portable vs. nonportable equipment, adequate selection of muscles type of action, lack of multiple surface electromyograms, and dynamic vs. isometric actions), among others (28,32,49,55,59,77,85,86), may help to explain the high prevalence of muscle activation outcomes not responsive to PJT. Furthermore, the sEMG-force relationship is best described as curvilinear with a plateau starting at the near maximal force range (8,68), which diminished its sensitivity to change with maximal or near maximal contractions.…”
Section: Sex Of Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, regardless of sex, it is striking that most of the muscle activation outcomes analyzed in the studies included in this review demonstrated no significant changes. It is possible that certain limitations related to assessment techniques (e.g., sensitivity of the equipment used to measure sEMG, use of portable vs. nonportable equipment, adequate selection of muscles type of action, lack of multiple surface electromyograms, and dynamic vs. isometric actions), among others (28,32,49,55,59,77,85,86), may help to explain the high prevalence of muscle activation outcomes not responsive to PJT. Furthermore, the sEMG-force relationship is best described as curvilinear with a plateau starting at the near maximal force range (8,68), which diminished its sensitivity to change with maximal or near maximal contractions.…”
Section: Sex Of Subjectsmentioning
confidence: 99%
“…It is possible that other adaptations, such as mechanical (e.g., musculotendinous stiffness) (87), motor skill (e.g., joint angle and intermuscular coordination) (3), anatomical (e.g., muscle fiber pennation angle) (59), or hypertrophy-related (37), may help to explain the improvements in physical fitness after PJT when muscle activation outcomes displayed no significant changes. Alternatively, certain limitations related to assessment techniques, such as the sensitivity of the equipment used to measure sEMG, inadequate selection of muscles type or action, lack of multiple surface electromyograms, and among others (28,49,55,59,77,85,86), may also help to explain the commonly observed high proportion of sEMG-related measures nonresponsive to PJT. In addition, nonoptimal PJT prescription might be a potential reason for the high prevalence of nonresponsive muscle activation outcomes.…”
Section: Studies With Low Responsiveness Of Muscle Activation Outcomementioning
confidence: 99%
“…This study uses a demographic data questionnaire and a muscle strength sensor observation sheet based on Arduino Uno with an Android application (Karimpour, Parsaei, Rojhani, Sharifian, & Yazdani, 2019). This study uses a demographic data questionnaire and an Arduino Uno based power sensor observation sheet with an Android application.…”
Section: Instrumentsmentioning
confidence: 99%
“…Recent advances in smart portable devices such as mobile phones have shown the great capability of facilitating and decreasing the cost, particularly in academic environments. Also, performance is promising to use the app for teaching purposes [ 11 ]. Chhabra et al in their study claimed that health applications were promising tools for improving outcomes in patients suffering from various chronic conditions.…”
Section: Introductionmentioning
confidence: 99%